Math Problems

## Questions

 $$y = 2 x^2 -3 x -2$$ $$y = x^2 -2 x -24$$ $$y = x^2 -5 x$$ $$y = 4 x^2 + 5 x + 1$$ $$y = 2 x^2 -8 x + 6$$ $$y = x^2 -3 x -10$$ $$y = x^2 -6 x + 5$$ $$y = 4 x^2 + 14 x + 6$$ $$y = 3 x^2 + 8 x -3$$ $$y = x^2 + 4 x -12$$ $$y = 2 x^2 -2$$ $$y = 2 x^2 + 4 x -6$$ $$y = x^2 -6 x$$ $$y = x^2 -5 x + 4$$ $$y = 4 x^2 -7 x -2$$ $$y = 4 x^2 + 4 x$$ $$y = 4 x^2 -2 x$$ $$y = x^2 -2 x -3$$ $$y = 3 x^2 + 3 x -6$$ $$y = x^2 -x -30$$ $$y = 3 x^2 -5 x -2$$ $$y = x^2 -x -20$$ $$y = x^2 + 2 x + 1$$ $$y = 3 x^2 + 7 x + 2$$ $$y = x^2 -4 x + 4$$ $$y = x^2 + 2 x -24$$ $$y = x^2 -4 x + 3$$ $$y = 3 x^2 -10 x + 3$$

 $$y = 2 x^2 -3 x -2$$ ⇒ $$(2 x + 1)(x -2)$$ $$y = x^2 -2 x -24$$ ⇒ $$(x -6)(x + 4)$$ $$y = x^2 -5 x$$ ⇒ $$(x -5)(x)$$ $$y = 4 x^2 + 5 x + 1$$ ⇒ $$(4 x + 1)(x + 1)$$ $$y = 2 x^2 -8 x + 6$$ ⇒ $$2(x -1)(x -3)$$ $$y = x^2 -3 x -10$$ ⇒ $$(x + 2)(x -5)$$ $$y = x^2 -6 x + 5$$ ⇒ $$(x -5)(x -1)$$ $$y = 4 x^2 + 14 x + 6$$ ⇒ $$2(2 x + 1)(x + 3)$$ $$y = 3 x^2 + 8 x -3$$ ⇒ $$(3 x -1)(x + 3)$$ $$y = x^2 + 4 x -12$$ ⇒ $$(x + 6)(x -2)$$ $$y = 2 x^2 -2$$ ⇒ $$2(x -1)(x + 1)$$ $$y = 2 x^2 + 4 x -6$$ ⇒ $$2(x -1)(x + 3)$$ $$y = x^2 -6 x$$ ⇒ $$(x)(x -6)$$ $$y = x^2 -5 x + 4$$ ⇒ $$(x -4)(x -1)$$ $$y = 4 x^2 -7 x -2$$ ⇒ $$(4 x + 1)(x -2)$$ $$y = 4 x^2 + 4 x$$ ⇒ $$4(x)(x + 1)$$ $$y = 4 x^2 -2 x$$ ⇒ $$2(2 x -1)(x)$$ $$y = x^2 -2 x -3$$ ⇒ $$(x -3)(x + 1)$$ $$y = 3 x^2 + 3 x -6$$ ⇒ $$3(x -1)(x + 2)$$ $$y = x^2 -x -30$$ ⇒ $$(x + 5)(x -6)$$ $$y = 3 x^2 -5 x -2$$ ⇒ $$(3 x + 1)(x -2)$$ $$y = x^2 -x -20$$ ⇒ $$(x + 4)(x -5)$$ $$y = x^2 + 2 x + 1$$ ⇒ $$(x + 1)(x + 1)$$ $$y = 3 x^2 + 7 x + 2$$ ⇒ $$(3 x + 1)(x + 2)$$ $$y = x^2 -4 x + 4$$ ⇒ $$(x -2)(x -2)$$ $$y = x^2 + 2 x -24$$ ⇒ $$(x -4)(x + 6)$$ $$y = x^2 -4 x + 3$$ ⇒ $$(x -3)(x -1)$$ $$y = 3 x^2 -10 x + 3$$ ⇒ $$(3 x -1)(x -3)$$